Performance of thermally modified wood strands and thin veneers for use in durable mass timber panels - Rajan Adhikari; Avishek Chanda; Muhammad Khusairy Bin Bakri; Modupe Morenike Akinnuoye; Manuel Raul Pelaez-Samaniego; Matthew Aro; Vikram Yadama (Case Studies in Construction Materials)
The innovative structural composite material, proposed in this study, offers an opportunity to repurpose low-value, small-diameter trees by adopting strand-based technology into their production. Furthermore, the thermal modification of wood strands provides a natural alternative to chemical treatments, ensuring the production of dimensionally stable and durable mass timber products. In this study, to demonstrate the scaling up of the thermal modification process, the mechanical and physical performance of thermally modified (TM) wood strands subjected to varying temperatures and pressures in an industrial autoclave were evaluated, and their efficacy in producing thin wood-strand veneer composite materials was evaluated. Wood strands from low-grade spruce-pine-fir lumber were thermally modified at peak temperatures of 165°C, 170°C, and 180°C, keeping a constant pressure of 1.4 MPa, and at 165°C with 0.8 MPa. A dwell time of 2 h at these conditions was used in all treatments. The process was conducted using an industrial autoclave (12 m3 volume) with nitrogen gas. Based on the results, the treatment at 0.8 MPa and 165°C yielded strands with suitable quality and performance to produce composite panels. Driven largely by hemicellulose degradation and their partial extraction, a 35 % reduction in the equilibrium moisture content and 21 % increase in contact angle of the treated strands was observed along with no significant variation in tensile modulus, about 52 % reduction in tensile strength, and 91 % increase in brittleness index. TM wood strands produced veneers with improved bond performance and dimensional stability, where a reduction in thickness swelling of up to 38 %, an increase in internal bond strength by 37 %, no significant variation in flexural stiffness, a decrease in flexural strength by 37 %, and an increase in brittleness index by 54 % in the veneers were observed.